"Peterburški tekst" ruske književnosti kot ruska različica zgodbe o prostorskem obratu - Podlesnik, Blaž (Ars et humanitas, 2019)
The article discusses the understanding of the textual and non-textual space in the concept of the Petersburg Text of Russian literature (V. N. Toporov), which in our view represents an original Russian (late) structuralist variation of the spatial turn in literary sciences. In comparison with the Western tendencies in spatial literary sciences, that emphasise non-textual space and try to move away from textualism, the concept of Petersburg supertext implies a particular form of non-textual space, open to reflection of its semiotic nature. Created by a literary spatial conceptualisation, this geographical/cultural/perceived space also assumes an awareness of its own transgressive nature, which in structural poetics was one of the key features of the literary textual space. Confronting this ideas with various contemporary Western and Russian spatial approaches in literary science, we then outline the problem of a broader conceptualisation of non-textual space as a cultural phenomenon, that, much like any text, can be thought of in two different modes of semiosis. We argue that that modern spatial literary studies should also try to make space for this different kind of space.
Keywords: besedilni prostor; non-textual space; peterburški tekst; Petersburg Text; prostorski obrat; ruska književnost; Russian literature; spatial turn; textual space; transgresija; transgression; zunajbesedilni prostor